2017
DOI: 10.1088/1361-6595/aa6c35
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-catalyst interaction studied in a single pellet DBD reactor: dielectric constant effect on plasma dynamics

Abstract: A novel single dielectric pellet DBD that is designed to facilitate studying the interaction between plasmas and catalysts is presented. The influence of material dielectric constant on plasma dynamics across a range of applied voltages is determined through the use of electrical characterisation combined with videos of the discharge. Different discharge modes in nitrogen are observed and their behaviour is characterised. A particular focus is given to the phenomenon known as 'partial discharging'. This is whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 36 publications
12
83
0
Order By: Relevance
“…The literature values for the dielectric constant of the tested materials are presented in Table 1. Among all tested materials, BaTiO 3 possesses the highest dielectric constant (>1000) [18]. In general, the dielectric constant of ferroelectric materials, i.e., BaTiO 3 , can largely vary depending on the applied frequency and temperature.…”
Section: The Dielectric Constant Of the Packed Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature values for the dielectric constant of the tested materials are presented in Table 1. Among all tested materials, BaTiO 3 possesses the highest dielectric constant (>1000) [18]. In general, the dielectric constant of ferroelectric materials, i.e., BaTiO 3 , can largely vary depending on the applied frequency and temperature.…”
Section: The Dielectric Constant Of the Packed Materialsmentioning
confidence: 99%
“…According to the existing literature, different parameters such as dielectric constant, surface area, porosity, packing density, and the shape of the packing are considered as the parameters that effectively change the conversion and the yield of products [11][12][13][14][15][16][17]. Among all important properties of the packing, the dielectric property of the packing is one of the determining factors in creating a synergistic plasma-catalyst system [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was discoveredt hat ah igher voltage would lead to more surface reactions via the ER mechanism. Butterworth andA llen [62] studied the main plasma-catalyst interactions for severald ielectric materials that could be potentially used in the NTPNF process. One representative studies was performed by Zhu et al,w ho studied the air plasma for the treatment of the Ni/Al 2 O 3 catalyst.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%
“…However, its catalytic activity should also be taken into account based on previousevidences of plasmacatalysti nteractions. Butterworth andA llen [62] studied the main plasma-catalyst interactions for severald ielectric materials that could be potentially used in the NTPNF process. They found that the plasma discharge for these materials occurreda tt he poles of the electrode-pallet interface.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%
See 1 more Smart Citation